Developing literature review writing and citation practices through an online writing tutorial series: Corpus-based evidence - Li, Zhi; Makarova, Veronika; Wang, Zhengxiang (Frontiers in Communication, 2023)
Writing up a literature review in English can be a daunting task for non-native English-speaking graduate students due to the complexities of this academic genre. To help graduate students raise genre awareness and develop LR writing skills, a five-unit online tutorial series was designed and implemented at a large university in Canada. The tutorial focuses on the following features of the LR genre: logical structure, academic vocabulary, syntax, as well as citation practices. Each tutorial unit includes an interactive e-book with explanations, examples, quizzes, and an individual or collaborative LR writing assignment. Twenty-nine non-native English-speaking graduate students participated in the tutorials and completed five writing tasks. This study reports on their developmental trajectories in writing performance in terms of cohesion, lexical features, syntactic features, and citation practices as shown in three individual writing tasks. Corpus-based analyses indicate that noticeable improvements are observed in several features (e.g., use of connectives, range and frequency of academic vocabulary) across the participants’ writing samples. Meanwhile, citation analysis shows a steady increase of both integral and non-integral citations in the participants’ writing samples, as measured with occurrence by the number of sentences, along with a more diverse use of reporting verbs and hedges in their final writing samples. Pedagogical implications are discussed.